Case study method key issues, key texts - Gomm, Roger; Hammersley, Martyn; Foster, Peter, 1951- (London : SAGE, 2000)
Case study is an increasingly popular approach in social research. This book is a comprehensive guide to the current uses and importance of case study methods.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Methodology